Zenon z Werony, Mowa I 39 (II, 18) - Nocoń, Arkadiusz (Vox Patrum, 2019)
Oration On the feast of St. Arcadius (I, 39 [II, 18]) by Zeno of Verona is not only the primary source of information about this African Saint, but also an important argument for the African origin of the Bishop of Verona. It is also important when we look at the development of literature on martyrdom. Translation of this oration into Polish is the first in history.